Synthesis, Antitumor and Antiviral In Vitro Activities of New Benzotriazole-Dicarboxamide Derivatives - Ibba, Roberta; Piras, Sandra; Corona, Paola; Riu, Federico; Loddo, Roberta; Delogu, Ilenia; Collu, Gabriella; Sanna, Giuseppina; Caria, Paola; Dettori, Tinuccia; Carta, Antonio (Frontiers in Chemistry, 2021)
Cancer and viral infections continue to threaten humankind causing death worldwide. Hence, the discovery of new anticancer and antiviral agents still represents a major scientific goal. Heterocycles designed to mimic the chemical structure of natural pyrimidines and purines have been designed over the years, exerting their activity acting as false substrates on several different targets. We reported a series of bis-benzotriazole-dicarboxamide derivatives which inhibit viral helicase of poliovirus, and hence we planned structure modifications to obtain different series of new dicarboxamides. Here, the synthesis and characterization of 56 new compounds: 31 bis-benzotriazole dicarboxamides and 25 mono-substituted acidic derivatives are reported. The synthesized compounds were tested for their antiviral and antitumor activity. Mostly, compounds 4a, 4c and 4d showed antiviral activity against tested Picornaviruses, Coxsackievirus B5 and Poliovirus-1. Likewise, four derivatives (3b, 3d, 4d, 9b) showed notable antiproliferative activity inhibiting cell growth in two distinct antitumor screenings. Compound 3b was selected as the antitumor lead compound for the wide range of activity and the potency proved. The lead compound was proved to induce apoptosis in SK-MES1 tumor cells, in a dose-dependent manner.